Nano-structured Alumina-ZrO2 ceramic laminates - Acchar,Wilson (2019)
ABSTRACT In the last years many efforts have been expended to develop colloidal process that uses water instead of organic solvents in the tape casting process. In present work, alumina/zirconia laminated nanocomposites were fabricated by layer-by-layer method and using water-based tape casting process. Physical and mechanical properties as well as the fracture mode were investigated. The laminates consisted of stacked alumina and zirconia green sheets produced by thermopressing. The ceramic laminates were first heated at 450°C (organic elimination) and subsequently sintered in air at 1500°C during 1 h. The ceramic laminates showed a mechanical strength of approximately 103 MPa (AZAZA) and 44 MPa (ZAZAZ), respectively and an intergranular-transgranular mixed fracture mode.